The hidden sedimentary basin underneath the Quaternary volcanic unit in Bogor and Kendeng area - Erlangga Septama; C. Prasetyadi; A Abdurrokhim; T. Setiawan; P.D. Wardaya; R. Raguwanti; R. Ryacudu; A. Mulawarman; B. Adhiperdhana; I. Haryanto; M.G. Rahman; A. Novianto; J. Setiawan; Y. Sutadiwiria; M. Syaifudin; V.I. Rossa; R.R. Pratama (Berita Sedimentologi, 2021)
The Java Island is an active volcanic arc that experiences several volcanism episodes, which gradually changes from South to North from the Late Oligocene to Pleistocene, following the subduction of the Australian plates underneath the Eurasian plates. During the Eocene, the southern and northern part of Java was connected as one passive margin system with the sediment supply mainly comes from Sundaland in the north.  The compressional tectonics creates a flexural margin and a deep depression in the central axis of Java Island and acts as an ultimate deep-sea depocenter in the Neogene period. In contrast to the neighboring Northwest and Northeast Java Basins in the Northern edges of Java Island, the basin configuration in the East-West trending depression in median ranges of Java (from Bogor to Kendeng Troughs) are visually undetected by seismic due to the immense Quaternary volcanic eruption covers.Five focused window areas are selected for this study. A total of 1,893 Km sections, 584 rock samples, 1569 gravity and magnetic data, and 29 geochemical samples (rocks, oil, and gas samples) were acquired during the study. Geological fieldwork was focused on the stratigraphic unit composition and the observable features of deformation products from the outcrops. Due to the Paleogene deposit exposure scarcity in the Central-East Java area, the rock samples were also collected from the mud volcano ejected materials in the Sangiran Dome.The distinct subsurface configuration differences between Bogor and Kendeng Troughs are mainly in the tectonic basement involvement and the effect of the shortening on the formerly rift basin. Both Bogor and Kendeng Troughs are active petroleum systems that generate type II /III Kerogen typical of reduction zone organic material derived from transition to the shallow marine environment. The result suggests that these basins are secular from the neighboring basins with a native petroleum system specific to the palaeogeographical condition during the Paleogene to Neogene periods where the North Java systems (e.g., Northwest and Northeast Java Basin) was characterized by oxidized terrigenous type III Kerogen.